2004
DOI: 10.1111/j.0736-8046.2004.21613.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Reduced Application Time of Ovide Lotion (0.5% Malathion) Compared to Nix Creme Rinse (1% Permethrin) for the Treatment of Head Lice

Abstract: Our objective was to conduct a randomized, investigator-blinded evaluation of the pediculicidal and ovicidal activity of a reduced application time (20 minutes) of Ovide (0.5% malathion) compared to Nix (1% permethrin) in a south Florida population infested with Pediculus humanus capitis. Either Ovide or Nix was applied according to the label instructions. However, Ovide application time was reduced to 20 minutes. At day 8, subjects with live lice were re-treated with the same product and procedure as on day 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 25 publications
0
30
0
1
Order By: Relevance
“…It is available only by prescription as a lotion that is applied to dry hair, left to air dry, then washed off after 8 to 12 hours, although some study results have suggested effectiveness when left on for as short a time as 20 minutes. 37 Head lice in the United Kingdom and elsewhere have shown resistance to malathion preparations, which have been available for decades in those countries. 38,39 The current US formulation of malathion (Ovide lotion, 0.5%) differs from the malathion products available in Europe in that it contains terpineol, dipentene, and pine needle oil, which themselves have pediculicidal properties 25 and may delay development of resistance.…”
Section: Malathion (05%)mentioning
confidence: 99%
“…It is available only by prescription as a lotion that is applied to dry hair, left to air dry, then washed off after 8 to 12 hours, although some study results have suggested effectiveness when left on for as short a time as 20 minutes. 37 Head lice in the United Kingdom and elsewhere have shown resistance to malathion preparations, which have been available for decades in those countries. 38,39 The current US formulation of malathion (Ovide lotion, 0.5%) differs from the malathion products available in Europe in that it contains terpineol, dipentene, and pine needle oil, which themselves have pediculicidal properties 25 and may delay development of resistance.…”
Section: Malathion (05%)mentioning
confidence: 99%
“…In Israel (Mumcuoglu et al 1991), the efficacy of 14 products had been tested according to the manufacturer's instructions but with in vitro tests with raring body lice (Pediculus humanus humanus). Other similar ex vivo efficacy tests of pediculicides available on their market are as follows: one in Egypt (Abdel-Ghaffar et al 2010) on 13 anti-head-lice products, not according to the manufacturer's instructions and without testing ovicidal efficacy, another in the USA (Meinking et al 1986), testing the pediculicidal activity of six pediculicides but not according to the manufacturer's instructions.…”
Section: Discussionmentioning
confidence: 99%
“…The assay was performed in respect of the manufacturer recommendations on a laboratory colony of body lice (P. humanus humanus) and their eggs. In other similar studies, the contact time in the assay differed from the contact time recommended by the manufacturer (Meinking et al 1986;Meinking et al 2001;Heukelbach et al 2008aHeukelbach et al , 2009Abdel-Ghaffar 2010;Gallardo et al 2012).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…[10] Yet, concerns about emerging head lice resistance to permethrin worldwide have been raised. [11][12][13][14][15][16][17][18] It is also clear that as permethrin resistance increases, its effectiveness for lice treatment is correspondingly reduced. Moreover, the information regarding the specific susceptibility or resistance of head lice in a particular geographical area is not readily available for both the public and health providers.…”
Section: Introductionmentioning
confidence: 99%